2012
DOI: 10.9790/5728-0330713
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Malaria Transmission in North Senatorial Zone of Taraba State Nigeria

Abstract: This research deals with mathematical modelling of malaria transmission in North Senatorial R , which is greater than 0, implies that the force of malaria infection in TarabaNorth Senatorial Zone is high. The researchers also make recommendations for the reduction of malaria in the zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A variety of plasmodium parasites exist. Mainly four types of plasmodium cause malaria disease among the human viz., falciparum, vivax, ovale and plasmodium malaria [1,11,12,13,14,19]. [17,22,23,24,25,26] developed a mathematical model to study the transmission of malaria; in fact, their study showed clearly that effective treatment offered to about fifty percent of the infected population together with about fifty percent prevention rate is all that is required to eliminate the disease.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of plasmodium parasites exist. Mainly four types of plasmodium cause malaria disease among the human viz., falciparum, vivax, ovale and plasmodium malaria [1,11,12,13,14,19]. [17,22,23,24,25,26] developed a mathematical model to study the transmission of malaria; in fact, their study showed clearly that effective treatment offered to about fifty percent of the infected population together with about fifty percent prevention rate is all that is required to eliminate the disease.…”
Section: Introductionmentioning
confidence: 99%